Lecturing in a Nursing School: Expectations and Constraints between Research and Practice - Cristina Barroso Pinto; Fátima Segadães; Regina Pires; Isilda Ribeiro; Palmira Oliveira (Medical Sciences Forum, 2022)
Nursing finds the basis for its action in research. The main purpose of research is to discover how to improve nursing care. Nurses are required to provide quality care based on the latest scientific evidence. We expect higher education institutions to develop scientific research; therefore, there seems to be a close relationship between research and teaching. Reconciling these two dimensions is not an easy task. This study demonstrates the close relationship between research and teaching. However, it also highlights some constraints related to the small number of full-time researchers and the difficulty reconciling research and teaching.